Respect: what is in my world (story on human values that everyone should do) - Trindade, Katia (New horizons, cedic international Islamabad, 2013)
A collection of heartwarming tales designed to teach children the timeless principles that shape a compassionate, respectful, and kind society. Each story focuses on a different human value$1 (Bsuch as kindness, empathy, honesty, responsibility, and fairness$1 (Bdemonstrating how these values can be practiced in everyday life. Through relatable characters and simple, engaging narratives, children learn that small acts of goodness can make a big difference, not just in their own lives but in the world around them. This series encourages young readers to internalize these values and take them to heart, helping them grow into thoughtful, caring individuals who understand the importance of treating others with respect and kindness. With each new story, children are inspired to make the world a better place, one positive action at a time.s